2015
DOI: 10.3109/14756366.2015.1016510
|View full text |Cite
|
Sign up to set email alerts
|

Crocus cancellatus subsp. damascenus stigmas: chemical profile, and inhibition of α-amylase, α-glucosidase and lipase, key enzymes related to type 2 diabetes and obesity

Abstract: Spices are appreciated for their medicinal properties besides their use as food adjuncts to enhance the sensory quality of food. In this study, Crocus cancellatus subsp. damascenus was investigated for its antioxidant activities employing different in vitro systems. Stigma extract demonstrated a radical scavenging activity against both 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radicals with IC 50 values of 34.6 and 21.6 mg/mL and a good ferric red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…29 Interestingly, it has been reported that saffron may reduce glucose absorption enzymes and as a result can improve diabetes control. 30 It is suggested that IFN-γ producing T helper lymphocytes (Th1) and IL-17 producing T helper cells (Th17) cells effectively participate in the pathogenesis of T1D. 31 On the other hand, it has been revealed that inflammatory process in the early stages of T1D is initiated by IL-17 which leads to huge infiltration of multiple inflammatory cells such as Th1 into the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…29 Interestingly, it has been reported that saffron may reduce glucose absorption enzymes and as a result can improve diabetes control. 30 It is suggested that IFN-γ producing T helper lymphocytes (Th1) and IL-17 producing T helper cells (Th17) cells effectively participate in the pathogenesis of T1D. 31 On the other hand, it has been revealed that inflammatory process in the early stages of T1D is initiated by IL-17 which leads to huge infiltration of multiple inflammatory cells such as Th1 into the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive postprandial glucose excursions are a known risk factor for developing diabetes [11]. One interesting approach for limiting the excursion is to inhibit the activity of digestive enzymes of glucose production such as α -amylase and α -glucosidase [12]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Crocus cancellatus subsp. damascenus extract with main constituents of catechin, ferulic and caffeic acids, induced 50.39% of inhibition of lipase activity at 5 mg/mL (Loizzo et al, 2016). The acetic extracts of Aronia melanocarpa L. and its cyanidin-3-glucoside fraction exhibited pancreatic lipase inhibitory activities with IC50 values of 83.45 and 1.74 mg/mL, respectively (Worsztynowicz et al, 2014).…”
Section: Resultsmentioning
confidence: 99%